PENGUKUR SUHU TUBUH SECARA TAK SENTUH MENGGUNAKAN INFRAMERAH BERBASIS ARDUINO UNO - , PAULUS PULIANO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The needs in the medical aspect of the modern tools that used in patients diagnose nowadays is growing fastly. The measurement of human body temperature is done using mercury based body thermometer. There are many kinds of body thermometer like non digital mercury thermometer and digital mercury thermometer. Mostly of the body temperature measuring methodes need one until two minutes to acquire the nilai of body temperature. The writer trying to build a tool that could measure the temperature of human body with faster way without sacrificing the accuracy. The writer trying to build a tool that can be used to measure human body temperature in the fast and accurate way. Using infrared thermometer sensor made by Melexis MLX90614 series based on arduino uno and LCD 16x2 as the informator is the way to make the idea realized. This tool has accuracy nilai 0.37 when tested and compared with human body temperatur. It is operated by creating short distance about 1 â 5 cm between the tools and the human part of body without make a physical contact. In 5 second the nilai of human body temperature could be read. This way is the milestone of the human body measurement.